"One Musician at a Time": Music, Philanthropy, and Public Policy in the Age of Coronavirus - Chapman, Dale (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Dale Chapman discusses the important work that the Jazz Foundation of America is doing during the pandemic, assisting jazz musicians with housing costs, medical expenses, and emergency financial support, and argues for the pandemic as an opportune moment to organize on behalf of policies that ensure the universal reach of economic and social security.